Composition Portfolio Commentary - Kenworthy, Jack Luke / JK (2021)
This portfolio of work aims to explore the physics of sound and psychoacoustics as a means for musical composition, utilising experimental music techniques and electronic music. These four binaural, acousmatic pieces take inspiration from spectral music, acoustic phenomena, minimalism, ambient music, beating tones, and space as a compositional parameter. The structure of this commentary will begin with a brief outline of my personal reasons for creating this music before examining some historical context and key terms surrounding the works. Finally, I will discuss my four compositions.